The library projects realized to the Institute jubilee - E. V. Beskaravainaya; T. N. Kharybina (Библиосфера)
The Library of Natural Sciences of the Russian Academy of Sciences (RAS) (a division of Pushchino Research Center RAS) has implemented several large-scaled projects in the light of preparing to celebrate the anniversary of the Institute of Protein Research RAS. Among them is a bibliometric analysis of publication activity of all researchers of the Institute including the information on the publications number, international cooperation, highly cited publications, distribution of papers by quartiles of the publishers with providing this information at the library website. Due to the interest shown in invention activities, we have analyzed the patents' thematic areas of the Institute. Another aspect of the study was to set up a portal on scientific schools of the Institute of Protein Research, which highlights the scientific area and schools significance, the leaders' part in every school, scientific papers of schools and its fellows, awards and honours, defended theses, bibliometric analysis of publications. The next research direction was to create a data base on the former researchers who live abroad in order to invite research scientists-compatriots to establish scientific-professional contacts.